The Effect of A Proposed Apparatus for Developing Motor Speed in Volleyball Players - Khairulla, Mohammed; Abdul Ilah, Maher (Journal of Physical Education, 2021)
Through the researchers’ observation of volleyball players’ motor response training especially that of Al Jaish Sport Club, they found that most training were traditional and do not depend on modern updated equipment. The aim of this research was to design an apparatus for developing a motor response in volleyball players. The subjects were (7) volleyball players from Al Jaish sport club and after applying a group of exercises the results showed that using the proposed apparatus has a positive effect on developing motor response speed in the subject under study.